THE INFLUENCE OF PERCEPTIONS OF QUALITY AND SOCIAL MEDIA ON BRAND EQUITY OF HONDA MATIC MOTORCYCLES AMONG STUDENTS OF UIN SJECH M. DJAMIL DJAMBEK BUKITTINGGI - Husna, Rizka Hayatul; Awaluddin, Awaluddin (REVENUE: Jurnal Manajemen Bisnis Islam, 2024)
This research was motivated by the large number of reports about the frames of Honda brand automatic motorbikes being rusty and broken. Various groups, including students, are discussing Honda brand automatic motorbike products because there are many negative reviews regarding the perception of product quality circulating on social media. This type of research is quantitative research with a survey method. The sampling technique used purposive sampling with a sample of 100 respondents who were students at UIN Sjech M. Djamil Djambek Bukittinggi who used Honda automatic motorbikes. Data collection was carried out by distributing questionnaires online via Google Form. Data analysis was carried out with the help of IBM SPSS version 25 software, by conducting research instrument tests, classical assumption tests, multiple linear regression tests and hypothesis tests. The aim of this research is to test and analyze partially and simultaneously the influence of the independent variables perception of quality and social media on the dependent variable brand equity of Honda automatic motorbikes among students at UIN Sjech M. Djamil Djambek Bukittinggi. The results of the research show that the t-test of the perceived quality variable has a calculated t-value (7.584) > t-table (1.98472) with a significance value of 0.000 < 0.05, so partially perceived quality has a positive and significant effect on brand equity. The t-test of the social media variable has a calculated t-value (3.188) > t-table (1.98472) with a significance value of 0.002 < 0.05, so partially social media has a positive and significant effect on brand equity. The F-test of the perceived quality and social media variables has an F-count value (79.980) > F-table (3.09) with a significance value of 0.000 < 0.05, so simultaneously the perceived quality and social media variables have a positive and significant effect on brand equity. Calculation of the coefficient of determination value shows that perceived quality and social media simultaneously influence brand equity by 62.3%